Thorp and Covich's freshwater invertebrates. - Damborenea, Cristina; Thorp, James H.; Rogers, D. Christopher (Academic Press, 2020)
Thorp and Covich's Freshwater Invertebrates, Volume 5: Keys to Neotropical and Antarctic Fauna, Fourth Edition, covers inland water invertebrates of the world. It began with Ecology and General Biology, Volume One (Thorp and Rogers, editors, 2015) and was followed by three volumes emphasizing taxonomic keys to general invertebrates of the Nearctic (2016), neotropical hexapods (2018), and general invertebrates of the Palearctic (2019). All volumes are designed for multiple uses and levels of expertise by professionals in universities, government agencies, private companies, and graduate and undergraduate students. Key Features: Includes zoogeographic coverage of the entire Neotropics, from central Mexico and the Caribbean Islands, to the tip of South America ; Provides identification keys for aquatic invertebrates to genus or species level for many groups, with keys progressing from higher to lower taxonomic levels ; Contains terminology and morphology, materials preparation and preservation, and references. --